A qualitative exploration on the awareness and knowledge of stakeholders towards Urban Heat Island phenomenon in Greater Kuala Lumpur: Critical insights for urban policy implications - Ramakreshnan, Logaraj; Aghamohammadi, Nasrin; Fong, Chng Saun; Ghaffarianhoseini, Amirhosein; Wong, Li Ping; Noor, Rafidah Md; Hanif, Noor Rosly; Wan Abd Aziz, Wan Nor Azriyati; Sulaiman, Nik Meriam Nik; Hassan, Norhaslina (Elsevier, 2019)
Despite its notable role in the exacerbation of urban climate, Urban Heat Island (UHI) was poorly addressed, communicated and integrated into local urban policies of many developing countries. Such scenario often queried the level of UHI understanding amongst the key players who were involved in urban policy formulation. Hence, a qualitative study using Focus Group Discussions (FGD) was designed to investigate the awareness and knowledge level of stakeholders such as policy makers and practitioners in Greater Kuala Lumpur (GKL), an expanding socio-economic hub of a developing tropical country. The findings demonstrated a variable lack of awareness and knowledge about the concept of UHI, its status in GKL as well as organizational engagement in adaptation and mitigation initiatives among the study participants. Essentially, policy makers illustrated a facile awareness and knowledge towards UHI issues whereas practitioners displayed a more robust portfolio of factual understanding regarding the corresponding issues. In line with National Urbanization Policy's (NUP) aspiration to optimize urban developments that provide high quality of life, this study sheds some light on the exigency for UHI awareness creation and capacity building among the policy makers. This study also provides impactful prepositions for the articulation of necessary actions towards evidence-based urban policy formulation in future. © 2019